Analysis of Anisa Sopiah's Personal Branding on Educational Content on TikTok Social Media - Nadia, Faizatun; Muyasaroh, Siti (Universitas Islam Balitar, 2024)
This research aims to analyze Anisa Sopiah's personal branding on educational content on TikTok social media using personal branding theory proposed by Peter Montoya, which includes 8 main concepts in building personal branding: (1) specialization, (2) leadership, (3) personality, (4) differences, (5) visibility, (6) unity, ( 7) steadfastness, (8) good name. The research method used is a descriptive qualitative approach, using interview techniques, observation and document study to collect data that focuses on the personal branding concepts applied by Anisa Sopiah in the educational content she uploads. The results show that Anisa Sopiah effectively applies all eight main concepts of personal branding to her educational content on TikTok, with a special emphasis on the concept of specialization that creates a professional and credible image in the eyes of her audience. The findings are expected to provide insights for educational content creators about the importance of building effective personal branding on social media, especially on the TikTok platform.